European Expert Buyersâ€™ Perceptions of New Zealand Agri-food Products and Businesses: An Explanation of the Theory of Buyer-Seller Relationships and Country of Origin Theory - Xiaomeng Sharon Lucock; Tim Baird; David Dean; Jeremy White (Jurnal Internasional Penelitian Bisnis Terapan, 2021)
With agrifood export earnings so pivotal to New Zealand (NZ)â€™s economy, understanding how expert buyers perceive the countryâ€™s agrifood products and businesses is imperative. This holds particularly true for the European Union (EU), being one of NZâ€™s main trading partners. This research draws on the key theories centering on buyer-seller relationships and Country of Origin (CoO) theory, investigating specifically the perceptions of NZ agrifood products and businesses held by European expert buyers who have different levels of knowledge and experience. A quantitative survey was conducted which investigated these perceptions held by the European expert buyers accessed in-person at a trade show in 2015 in Germany. Bipolar adjective scales were used to test product and business attributes. One-way ANOVAâ€™s were adopted to test for perceptual differences between European buyers with high/medium/low experience with New Zealandâ€™s agrifood products and/or businesses. Overall, New Zealand agrifood products and businesses were viewed positively from the perspective of European expert buyers, with the degree of positivity increasing as the level of experience increased. This study also highlighted the need for future research on how CoO affects buyer-seller relationships, especially via the concept of the â€œhalo effectâ€.